2007
DOI: 10.1007/s11146-007-9062-6
|View full text |Cite
|
Sign up to set email alerts
|

The Inflation Hedging Characteristics of US and UK Investments: A Multi-Factor Error Correction Approach

Abstract: Investment returns, Real estate, Inflation hedging, Error correction model,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
76
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 56 publications
12
76
1
Order By: Relevance
“…Employing a multi-factor error correction approach, Hoesli et al (2008) examined the inflation characteristics of US and UK property investments, and concluded that in US, inflation has a positive coefficient, but there exists little evidence of short term adjustments of property prices to changes in inflation. The results for UK were similar to that of the US, and was in line of those obtained earlier by Stevenson (2000) who used OLS models, cointegration and causality techniques to conclude that house prices and inflation share a common long-run trend and are indeed cointegrated.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Employing a multi-factor error correction approach, Hoesli et al (2008) examined the inflation characteristics of US and UK property investments, and concluded that in US, inflation has a positive coefficient, but there exists little evidence of short term adjustments of property prices to changes in inflation. The results for UK were similar to that of the US, and was in line of those obtained earlier by Stevenson (2000) who used OLS models, cointegration and causality techniques to conclude that house prices and inflation share a common long-run trend and are indeed cointegrated.…”
Section: Related Literaturementioning
confidence: 99%
“…Results may vary across time periods, market conditions, characteristics of the countries in question and different components of returns, as well as, the various variables that are included in the modelling exercises (Hoesli et al 2008). …”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of real estate inflation-hedging properties has been widely documented in many countries (see for example, Barkham, 1996;Tarbert, 1996;Ganesan, 1998;Stevenson, 2000;Hoesli, 2008,). In…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with REITs shows same signs for those variables. Using data for the U.S. and the U.K., Hoesli, Lizieri & MacGregor (2008) also document positive linkages with GDP and emphasize the role of direct real estate as an inflation hedge contrasting with the so-called perverse inflation hedge of listed real estate.…”
Section: Literature Reviewmentioning
confidence: 77%